REDISTRIBUSI TANAH MENUJU PENGUASAAN TANAH YANG BERKEADILAN - Broto, subroto (JURNAL ILMIAH LIVING LAW, 2015)
The goals to be achieved in this research is to study and analyze how the transition arable land rights on ex leasehold land, to study and analyze the impact arising from disputes over land arable land in the former concession , to determine and analyze the arable land in dispute resolution above ground with the perspective of ex leasehold land redistribution . The method used is empirical juridical, juridical approach is used as a baseline in the form of rules relating to the rights and land acquisition, while the empirical approach used to analyze how the process of the issues raised. Settlement of land disputes are often detrimental to the community , the need to encourage settlement through land redistribution. This is the answer to the problem of inequality emerging agrarian structure , poverty , food security and rural development . Land redistribution as a development strategy and is expected to step in solving the fundamental problems and at the same time able to realize a more equitable life together.